Usage of uv-curable soybean oil based coating formulations for pretreated cotton fabrics - YILDIZ, ZEHRA (My University, 2022)
This study aims to design an alternative way for the laminated fabric manufacturing with a cleaner production method, by using a bio-based coating formulation and time/cost saving, environmentally friendly UV-curing technology, compared to the conventional petroleum based, heat and solvent requiring laminating process. For this purpose, acrylated epoxidized soybean oil oligomer was synthesized and included in coating formulations for the application on cotton fabrics via UV-curing. The obtained oligomer was characterized by FTIR and NMR spectroscopies. In order to enhance the bonding between the fabric and coating layer, fabrics were pretreated by sodium hydroxide, pectinase enzyme, and a commercial washing agent prior to the coating process. The effects of pretreatment methods on the wettability, tensile and peel strength, and abrasion resistance of the fabrics were all examined before/after coating process. Enzyme pretreatment revealed promising results by increasing the surface roughness, fibrillation, and hydrophilicity of the cotton fabrics. After coating and UV-curing process, the highest increment in tensile strength, the highest peel strength, and the least weight loss value against abrasion were all recorded in enzyme pretreated fabric.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Engineering and Technology; MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; Soybean oil; cotton fabric; uv-curing; pectinase enzyme; peel test; IN-SITU SYNTHESIS; EPOXY ACRYLATE; MECHANICAL-PROPERTIES; CARBON NANOTUBES; NANOCOMPOSITES; METHACRYLATES; PERFORMANCE; RESINS